Hydroxyapatite (HAp) From Tenggiri Fish Bones As Abrasive Material In Toothpaste Formula - Lia Anggresani; Yoli Nopita Sari; Rahmadevi Rahmadevi (Syarif Hidayatullah State Islamic University, 2021)
Cavities are one of the factors of dental and oral health problems that can be prevented by brushing teeth using toothpaste. Toothpaste can be made from a variety of chemicals, one of which is hydroxyapatite (HAp) which has good biocompatible properties. Hydroxyapatite can be obtained by utilizing tenggiri fish bone waste which has the main element of calcium. Fish bones soaked with NaOH and acetone are then calcined at 800 °C for 3 hours to obtain CaO powder and characterized its elemental content using X-Ray Fluorescence (XRF). CaO obtained was then reacted with (NH4)2HPO4 with a mole ratio of Ca/P 1.67 then heated at 90 °C, added NaOH up to pH 12, then the obtained deposits are filtered and calcined at 900 °C. The solids obtained from the calcination are then characterized using X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). Hydroxyapatite (HAp) was formulated into toothpaste with the concentrations of 0% (F0), 45% (F1), 50% (F2), and 55% (F3). Toothpaste was evaluated using organoleptic tests, homogeneity tests, foam height tests, dispersability tests, pH and hedonic tests. XRD analysis shows that the resulting hydroxyapatite (HAp) has a crystal structure in accordance with ICSD standard No. 96-900-3549. SEM analysis showed that granular particles measuring 0.1 μm–0.3 μm in size. All formulated toothpastes (F0, F1, F2, and F3) meet the requirements of a good toothpaste. Hydroxyapatite (HAp) can be formulated into a good toothpaste with a concentration of 45%.